BFS of GICs for ART heated with LED during setting - Molina, Gustavo Fabián (2013)
Fil: Molina, Gustavo Fabían. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra de Materiales Dentales; Argentina.